A hybrid green energy-based system with a multi-objective optimization approach for optimal frost prevention in horticulture. (20th December 2021) - Atam, Ercan; Abdelmaguid, Tamer F.; Keskin, Muhammed Emre; Kerrigan, Eric C.
Abstract: Frost affects horticultural plants considerably and result in multi-dimensional harms: from economic losses to psychological problems for people involved in horticulture. As a result, prevention of frost in horticulture is of utter most importance for many countries. In this paper, first we propose a novel green energy-integrated solution, a hybrid renewable energy-based system involving active heaters, for this less studied, but very important problem. We then develop a multi-objective robust optimization-based formulation for optimization of the proposed system in order to (i) optimize the distribution of a given number of active heaters in a given large-scale orchard to optimally heat the orchard by the proposed frost prevention system and (ii) optimize the layout of the thermal energy distribution network to minimize the total pipe length (which is directly related to the installation cost and the cost of energy losses during energy transfer). Finally, the resulting optimization problem is approximated using a discretization scheme. A case study is provided to give an idea of the potential savings using the proposed optimization method compared to the result from a heuristic-based design, which showed a 24.13% reduction in the total pipe length and a 54.29% increase in optimal heating. Compared to current active frost prevention methods, the proposed hybrid green energy system for frost protection is a cleaner, environmentally friendly and potentially cost-effective solution. Highlights: A hybrid green energy system is proposed for frost prevention in large fruit orchards. The proposed system is a cleaner and potentially cost-effective solution. A multi-objective robust optimization framework for system optimization is developed. A case study is presented for a large apricot orchard located in Malatya, Turkey. 24.13% reduction in pipe length and 54.29% increase in optimal heating are achieved.